2022
DOI: 10.3389/fgene.2022.940292
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Whole-Exome Sequencing-Based Copy Number Variation Analysis Identified a Novel DRC1 Homozygous Exon Deletion in a Patient With Primary Ciliary Dyskinesia

Abstract: Objective: Whole-exome sequencing (WES) based copy number variation (CNV) analysis has been reported to improve the diagnostic rate in rare genetic diseases. In this study, we aim to find the disease-associated variants in a highly suspected primary ciliary dyskinesia (PCD) patient without a genetic diagnosis by routine WES analysis.Methods: We identified the CNVs using the “Exomedepth” package in an undiagnosed PCD patient with a negative result through routine WES analysis. RNA isolation, PCR amplification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…More recently, Olfe et al have demonstrated CTLA-4 insufficiency due to a novel CTLA-4 deletion using ClinCNV ( German and Stephan, 2019 ; Olfe et al, 2023 ), further highlighting the synergy of CNV calling with WES analysis. Beyond the scope of autoimmune diseases, NGS techniques have also been extensively utilized in identifying causal variants (including CNVs) contributing to cancer ( van Dijk et al, 2014 ; Papp et al, 2021 ; Satam et al, 2023 ), congenital ( Lai et al, 2021 ; Li et al, 2022 ; Liu et al, 2022 ; Wang et al, 2022 ; Wu et al, 2022 ; Refeat et al, 2023 ), cardiovascular ( Hu et al, 2023 ) and hematological diseases ( Hassan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Olfe et al have demonstrated CTLA-4 insufficiency due to a novel CTLA-4 deletion using ClinCNV ( German and Stephan, 2019 ; Olfe et al, 2023 ), further highlighting the synergy of CNV calling with WES analysis. Beyond the scope of autoimmune diseases, NGS techniques have also been extensively utilized in identifying causal variants (including CNVs) contributing to cancer ( van Dijk et al, 2014 ; Papp et al, 2021 ; Satam et al, 2023 ), congenital ( Lai et al, 2021 ; Li et al, 2022 ; Liu et al, 2022 ; Wang et al, 2022 ; Wu et al, 2022 ; Refeat et al, 2023 ), cardiovascular ( Hu et al, 2023 ) and hematological diseases ( Hassan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%